Restitution of fresh organic matter to the soil by woody plants in the fields of ANR in the Maradi region of central eastern Niger - Ladi, Yahaya Alio Dan; Lamso, Nomaou Dan; Ado, Maman Nassirou; Iro, Dan Guimbo; Guero, Yadji (International Journal of Sustainable Agricultural Research, 2023)
Niger, like other Sahelian countries, has experienced severe droughts that have led to the disappearance of vegetation cover in most regions and have led populations to adopt restoration techniques. This is the case of the practice of assisted natural regeneration (ANR) developed in the Maradi region. The objective of this study is therefore to quantify the fresh organic matter (FOM) of woody plants in ANR fields. The study fields were selected in two ANR terroirs (Boussaragui and Dan Saga). The direct method was used to quantify litter inputs from trees, shrubs and woody clumps that contribute to soil organic carbon stock (SOCS). Tree litter was quantified by a trap door and tussock litter by collection after clearing. The results of this work show that litterfall in the dry season occurs throughout the season, at different times depending on the terroir, with a shift in production peaks between plots in the same terroir. The average dry season litter production is 265.52 and 937.62 kg. ha-1 for Boussaragui and Dan Saga respectively. Trees and shrubs produce more litter and thus return more FOM to the soil than do tussocks. This study thus reveals that woody plants in ANR fields contribute significantly to improving the organic carbon stock of cultivated sandy soils.